Improved direct torque control in dual inverters using flexible sector detector and duty cycle techniques - Aihsan, Muhammad Zaid (2024)
Direct Torque Control of Open-End Winding Induction Motor (DTC-OEWIM) is one of the techniques in motor drive applications that provides a robust and straightforward structure with excellent dynamic torque control. It controls the induction motor at both ends by using the dual-inverter circuit. Despite its outstanding performance, the DTC-OEWIM technique has several drawbacks. When the dual-inverter circuit is supplied with mismatched DC voltages, the direction of the medium voltage vectors will deviate and no longer tangential to the circular flux locus. This will causes significant stator flux droop and distortion in the stator currents, leading to poor torque regulation. Even though the DTC-OEWIM technique is famous for reducing torque ripples by using short voltage vectors, it is still unable to minimize them, especially during low-speed operations entirely. A flexible sector detector proposes to overcome the problems by generating a new sector that ensures the deviated voltage vectors are tangential to the circular flux locus. The study explored the potential of the proposed technique under steady-state and transient-state operation. Another objective was to design the duty cycle control technique to limit the surge torque slope during low-speed operation. Integrating duty cycle ratios into the default inverter switching restricts the torque increment and torque decrement rate. The proposed techniques were compared with the default DTC-OEWIM system and verified through simulation and experimental work. For simulation, MATLAB/Simulink software was used to design the complete system, using the exact parameters as in the hardware experimental setup. For experimental works, the setup consists of a dSPACE DS1104 controller, two units of a two-level inverter connected in a dual-inverter configuration, and a 1.1kW induction motor with a 2kW DC generator as a load. The results show a significant improvement: 1) the minimization of stator flux droop and distortion in stator currents, which in turn improves the torque regulation and 2) the reduction of torque ripples by up to 50% and the improvement in switching frequency during low-speed operation. In conclusion, the proposed technique effectively improves DTC-OEWIM while maintaining the simple structure of the DTC system.